M14 The effect of multidisciplinary therapy on cognition in premanifest huntington's disease: an exploratory study. (13th September 2016) - Cruickshank, Travis; Bartlett, Danielle; Lampit, Amit; Hoult, Linda; Govus, Andrew; Pulverenti, Tim; Rankin, Tim; Reyes, Alvaro; Domínguez D, Juan F; Kordsachia, Catarina; Power, Brian; Newton, Robert U; et al.
Abstract : Background: Despite immense scientific efforts, there are still no proven drug agents that delay or treat cognitive impairments in individuals with Huntington's disease (HD). Recent clinical and preclinical data suggests that environmental interventions have a positive impact on many cognitive domains that are affected by HD. There are, however, no empirical studies on the effect of environmental interventions on cognition in individuals with premanifest HD. Intervening during this early stage of the disease may support and/or boost cognitive abilities in affected individuals. Aims: To evaluate the effectiveness of a nine month multidisciplinary therapy intervention on cognition in individuals with premanifest HD. Methods: Eighteen individuals with premanifest HD (13 women, 5 men; 43 ± 13 years) undertook a multidisciplinary therapy intervention for nine months. The intervention consisted of three times weekly supervised aerobic and resistance exercise, dual task and computerised cognitive training. Participants were assessed using validated cognitive measures before and after the intervention. Results: Participants completed all mandatory training sessions throughout the study. Significant improvements in verbal learning and memory (Hopkins Verbal Learning Test), information processing speed (Symbol Digit Modalities Test), attention (Trail Making Test Part A), cognitive flexibility (Trail Making Test Part B) and problem solving (One Touch Stockings of Cambridge) were observed following the intervention. Conclusions: This study provides preliminary evidence on the positive effects of multidisciplinary therapy on cognition in individuals with premanifest HD. Larger controlled trials are, however, required to confirm these promising findings.